Peran Sistem Endokrin dalam Regulasi Fisiologis Tubuh dan Implikasinya terhadap Kesehatan - Anang Kurniawan; Setiawan Wisnu Aji; Dhionisius David Mario; Liss Dyah Dewi Arini (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Background: The endocrine system is a network of glands that produces body hormones to regulate various body functions, such as growth, metabolism, regulation reproduction, and homeostasis. This research aims to provide a comprehensive overview of the role of the endocrine system, the function of the hormones produced, and the impact of their disorders on health. The research was carried out using a literature study method of six relevant national journals published in the last five years. The results of the analysis show that the endocrine system plays an important role in maintaining body balance through feedback mechanisms and interactions with the nervous system. Disorders of glands such as the pancreas, thyroid and adrenals can lead to serious illnesses, including diabetes mellitus, hypothyroidism and Cushing's syndrome. This study emphasizes the importance of understanding the endocrine system for the development of early detection and intervention strategies for hormonal disorders. It is hoped that the research results can become a reference for medical personnel and scientists in improving the quality of public health.